RASIONALITAS PENGGUNAAN ANTIBIOTIK PADA TERAPI PNEUMONIA DI RUMAH SAKIT AKADEMIK UNIVERSITAS GADJAH MADA PERIODE JANUARI–JUNI TAHUN 2025 - Salma Karimah; Muhammad Nurul Fadel; Bintari Tri Sukoharjanti (Nusantara Hasana Journal, 2026)
Pneumonia remains a major infectious disease contributing to significant morbidity and mortality, especially among adults and elderly patients. Antibiotic therapy as the main treatment for pneumonia must be rational to ensure therapeutic effectiveness, reduce antimicrobial resistance, and improve clinical outcomes. Objective: This study aimed to analyze the rationality of antibiotic use in hospitalized pneumonia patients at Universitas Gadjah Mada Academic Hospital during January–June 2025 based on the National Guidelines for Adult Pneumonia Management 2023. This study used a descriptive non-experimental design with a retrospective approach. A total of 92 patients were selected using purposive sampling. Rationality evaluation was conducted based on appropriate patient, indication, drug, dose, and route of administration. Most patients were aged >60 years (56.5%), male (53.3%), and had comorbidities (97.8%). Antibiotic use evaluation showed 100% appropriate patient selection, 100% appropriate indication, 95.9% appropriate drug selection, 93.8% appropriate dosing, and 100% appropriate route of administration. Overall, rational antibiotic use was found in 86 patients (93.5%), while 6 patients (6.5%) were categorized as irrational. Antibiotic use in pneumonia patients at RSA UGM was generally rational, although inappropriate drug selection and dosing remained issues requiring attention to optimize antibiotic therapy.